Peranan Penatalayanan Administrasi Bagi Efektivitas Pelayanan Gembala Jemaat - Matius Julianes; Barthomius K Jiu; Mikha Agus Widiyanto (Jurnal Teologi Praktika, 2020)
Administration stewardship needs to be organized and managed properly. The availability of administrative data is very helpful for pastors in planning and designing pastoral care services, so as to support the realization of effective pastoral care services. This research aimed to examine the role of administrative stewardship for the effectiveness of the ministry of pastors. This research used a correlational method. The results showed that there was a positive and significant role of administrative stewardship for the ministry of the pastor effectiveness. Good stewardship administration with the availability of data that can be accessed easily and quickly, making pastoral care effective